Penerapan Model Lesson Study Pada Pembelajaran Pendidikan Agama Hindu Di Smp Saraswati 1 Denpasar - Putu Ayu Wulan Sri Diantary (Jurnal Penelitian Agama Hindu, 2019)
Learning activities are one of the activities that cannot be separated from education, especially learning Hinduism. In addition to teacher parents have an important role in developing the character of their students. It can be said that the purpose of education will be achieved if learning activities can take place well and maximally. The theory used to analyze the problem is the structural theory of functionalism by Artadi, structural functionalism theory by Nasikum, and structural functional theory by Triguna. Data collection methods are observation, interview, literature study, and documentation study. The collected data were analyzed using qualitative descriptive analysis method with steps of reduction, data presentation, and conclusion drawing. The results showed (1) the implementation of the action in stage II had run better compared to phase I. Some indicators that were lacking in achievement in class I could be improved, (2) weaknesses in the implementation of phase I lesson study the apparent weaknesses were in presenting learning, Model teachers still have very little to do with learning with the experience of everyday students and the use of the environment as a source of learning, stage II the ability of the model teacher to use various ways to generate enthusiasm for student learning (providing motivation). As far as possible students need to be encouraged to be able to organize their own learning and use interpersonal interactions with friends and teachers to develop cognitive / intellectual abilities and social abilities. This indicator gets less attention from the teacher, perhaps because in learning most of the students have shown activeness, (3) Factors that support the application of lesson study on the learning of Hindu Religion in Denpasar Saraswati 1 Middle School, namely 1) students learn actively; 2) innovative students; 3) creative students; 4) students who study effectively; 5) pleasant atmosphere; 6) teachers who teach; 7) the issuance of the Teacher and Lecturer Law; 8) collaborative arrangement of goals, attention to data collection about student learning, and agreements that provide opportunities for productive discussion on difficult issues.